The Mediating Role of Psychological Empowerment on the Relationship Between Digital Transformation, Innovative Work Behavior, and Organizational Financial Performance - Saqib Muneer; Ajay Singh; Mazhar Hussain Choudhary; Awwad Saad Alshammari (Behavioral Sciences)
With the use of digital technologies in today’s innovation era, the financial sector has transformed how they facilitate customer business and generate a high level of revenue. This study aims to explore the relationship between innovative work behavior (IWB), digital transformation (DT), and organizational financial performance (OFP) to analyze the mediating role of workers’ psychological empowerment (PE) between independent and dependent variables. Further, we examined the moderating role of smart technologies (ST) between PE and OFP. This study collected data from Saudi banking sector employees using a well-structured questionnaire adopted from previous literature. Next, Smart-PLS was used to analyze the data using the structural equation modeling-partial least squares (SEM-PLS) approach. The results reveal that IW positively relates to OFP, with PE mediating this relationship. Furthermore, DT positively affects OFP. ST acts as a positive moderator that enhances workers’ PE and OFP. Meanwhile, PE, as a mediator, positively relates DT and IWB to OFP. Overall, this study makes valuable theoretical, empirical, and practical contributions, which can benefit bank management, policymakers, and future academic research.